دور تسويق خدمة النقل في تحقيق التنمية المستدامة (دراسة حالة شركة الوحدة للنقل بحاسي مسعود) - ربوح, أم الخير; بن جروة, حكيم (جامعة الوادي - University of Eloued, 2015)
تهدف هذه الدراسة إلى محاولة إيجاد علاقة تسويق خدمة النقل بالتنمية المستدامة من خلال إبراز مساهمة النقل في تحقيق متطلبات البعد الاقتصادي والاجتماعي والبيئي، لتمكّن من الحصول على خدمات نقل تتسم بالجودة والكفاءة وتلبي احتياجات مختلف مستخدميها. حيث تمثلت الدراسة التطبيقية للتسويق والتنمية المستدامة في شركة الوحدة للنقل بحاسي مسعود- ورقلة. وقد توصلت الدراسة إلى أن دور تسويق خدمة النقل تتجلى في تحقيق متطلبات الأبعاد الاقتصادية والاجتماعية والبيئية للتنمية المستدامة، إلا أن هذا الأمر يبقى نسبياُ لعدم وجود مؤشرات للتنمية المستدامة تتعلق بنقل البضائع بصفة مطلقة ومرتبطة مباشرة بالموضوع. The aim of this study was to try to find a relationship marketing service transport to sustainable development by highlighting the contribution of transport to achieve the requirements of economic and social dimension and environmental, To be able to get transportation services are quality and efficiency and to meet the needs of different users. Where the study was applied for marketing and sustainable development in the company for the transfer of the unit Hassi Messoud Ouargla. The study found that the role of marketing service transport requirements are reflected in the achievement of economic and social dimensions of environmental and sustainable development, but that it remains relatively to the lack of indicators for sustainable development regarding the transfer of goods in absolute and directly linked to the subject
مقال
Keywords: النقل، المزيج التسويقي لخدمة النقل، التنمية المستدامة; transport, marketing mix to serve the transportation, sustainable development